2015
DOI: 10.1021/acs.nanolett.5b00133
|View full text |Cite
|
Sign up to set email alerts
|

General Strategy for Biodetection in High Ionic Strength Solutions Using Transistor-Based Nanoelectronic Sensors

Abstract: Transistor-based nanoelectronic sensors are capable of label-free real-time chemical and biological detection with high sensitivity and spatial resolution, although the short Debye screening length in high ionic strength solutions has made difficult applications relevant to physiological conditions. Here, we describe a new and general strategy to overcome this challenge for field-effect transistor (FET) sensors that involves incorporating a porous and biomolecule permeable polymer layer on the FET sensor. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
241
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 224 publications
(256 citation statements)
references
References 44 publications
(100 reference statements)
3
241
0
1
Order By: Relevance
“…2D). These results are consistent with previous observations for PEG-modified silicon nanowire FETs (25), and moreover, an estimate of the effective dielectric constant of the PEG layer (SI Text) supports the hypothesis that this permeable layer reduces the effective dielectric constant at sensor surface compared with aqueous solution.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…2D). These results are consistent with previous observations for PEG-modified silicon nanowire FETs (25), and moreover, an estimate of the effective dielectric constant of the PEG layer (SI Text) supports the hypothesis that this permeable layer reduces the effective dielectric constant at sensor surface compared with aqueous solution.…”
Section: Resultssupporting
confidence: 92%
“…In contrast, PEG/ETA-modified devices show only a gradual decrease in PSA-sensing signal with increasing PB concentration. The signal response in 100 mM PB, ∼14 mV, exceeds the signal recorded from ETA-modified devices in 10 mM PB, and moreover, well-defined sensing signals, ∼11 mV, can still be recorded in 150 mM PB where the Debye length is ∼0.5 nm (25). In addition, these data show that PSA sensing is reversible with the device conductance returning to baseline following addition of pure PB buffer, thus establishing that there is minimal irreversible protein binding to the modified graphene devices.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…I). [74][75][76][77]80] At the end of this review, we will discuss in details that recent progresses on operating GFETs at high frequencies suggested that Debye screening can be overcome: [46] 1.…”
Section: Debye Screeningmentioning
confidence: 99%
“…Possible routes to circumvent the Debye screening effect include short antibody design, porous polymer incorporation, and ex situ measurement in low ionic strength buffers (see Section 2.5). [74][75][76][77]80] These approaches, however, also impose limitations on the biodetection and it is highly desirable to develop a straightforward methods to overcome the Debye screening: [46] 1. without any special design or engineering of the receptor molecules and the sensor environments, and 2. in physiological conditions to facilitate in-situ, real-time biosensing. Theoretically, improved sensitivity is expected at high frequencies using a measuring strategy that overcomes the ionic screening effect.…”
Section: Overcoming the Debye Length Limitations With Radio-frequencymentioning
confidence: 99%